2014
DOI: 10.1007/s10571-014-0139-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circulating MicroRNAs as Potential Biomarkers for Detecting Acute Ischemic Stroke

Abstract: MicroRNAs (miRNAs) are present in serum and have the potential to serve as disease biomarkers. As such, it is important to explore the clinical value of miRNAs in serum as biomarkers for ischemic stroke (IS) and cast light on the pathogenesis of IS. In this study, we screened differentially expressed serum miRNAs from IS and normal people by miRNA microarray analysis, and validated the expression of candidate miRNAs using quantitative reverse-transcriptase polymerase chain reaction assays. Furthermore, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 56 publications
5
64
0
1
Order By: Relevance
“…In both studies cell culture experiments indicated that miR-124 is involved in apoptosis. Recently, Li et al [13] reported up-regulation of three miRNAs in serum of stroke patients including miR-1246, which had the highest fold change (FC = 13.6; p  = 0.01) in our NGS experiment. In summary, these results, although not fully comparable, support our findings.…”
Section: Discussionmentioning
confidence: 58%
“…In both studies cell culture experiments indicated that miR-124 is involved in apoptosis. Recently, Li et al [13] reported up-regulation of three miRNAs in serum of stroke patients including miR-1246, which had the highest fold change (FC = 13.6; p  = 0.01) in our NGS experiment. In summary, these results, although not fully comparable, support our findings.…”
Section: Discussionmentioning
confidence: 58%
“…In atherosclerotic diseases, it can inhibit the production of phosphatase and tensin homolog in vascular endothelial cells, blocking TNF-α–induced activation of caspase-3 and preventing endothelial cell apoptosis [77]. Serum miR-106b-5p has been shown to be a potential diagnostic biomarker for ischemic stroke [78]. miR-200c-3p, an important tumor-suppressive miRNA, can regulate cell-cycle mechanics and apoptosis in breast cancer and is a potential diagnostic biomarker distinguishing normal individuals from those with gastric cancer [79, 80].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic adjustment is a key event in early altitude acclimatization. Moreover, it is intriguing that differentially expressed microRNAs between pre- and pro-exposure to high altitude overlapped with those found in ischemic stroke patients (Li et al, 2015). This indicates that hypoxia sensitive cmiRNAs are prevalent in hypoxia related diseases.…”
Section: Discussionmentioning
confidence: 99%